What controls the large-scale magnetic fields of M dwarfs?. Issue Volume 9:Issue S302(2013) (7th August 2014) - Gastine, T.; Morin, J.; Duarte, L.; Reiners, A.; Christensen, U.; Wicht, J.
Abstract: Observations of active M dwarfs show a broad variety of large-scale magnetic fields encompassing dipole-dominated and multipolar geometries. We detail the analogy between some anelastic dynamo simulations and spectropolarimetric observations of 23 M stars. In numerical models, the relative contribution of inertia and Coriolis force –estimated by the so-called local Rossby number– is known to have a strong impact on the magnetic field geometry. We discuss the relevance of this parameter in setting the large-scale magnetic field of M dwarfs.